Dexmedetomidine Activates Akt, STAT6 and IRF4 Modulating Cytoprotection and Macrophage Anti-Inflammatory Phenotype Against Acute Lung Injury in vivo and in vitro - Chen Q; Sun Y; Sun Y; Liu X; Pac Soo A; Chang E; Sun Q; Yi B; Wang DX; Zhao H; Ma D; Qin Z; et al. (Dove Medical Press, 2022)
Qian Chen,1,2,* Zhigang Qin,1,* Yibing Sun,3 Xiangfeng Liu,1 Aurelie Pac Soo,2 Enqiang Chang,2 Qizhe Sun,2 Bin Yi,1 Dong-Xin Wang,3 Hailin Zhao,2 Daqing Ma,2 Jianteng Gu1 1Department of Anaesthesiology, Southwest Hospital, Third Military Medical University (Army Medical University), Chongqing, People's Republic of China; 2Division of Anaesthetics, Pain Medicine and Intensive Care, Department of Surgery and Cancer, Faculty of Medicine, Imperial College London, Chelsea & Westminster Hospital, London, UK; 3Department of Anaesthesiology and Critical Care Medicine, Peking University First Hospital, Beijing, People's Republic of China*These authors contributed equally to this workCorrespondence: Jianteng Gu, Department of Anaesthesiology, Southwest Hospital, Third Military Medical University, 30 Gaotanyan Road, Chongqing, People's Republic of China, Tel +86 23 68765366, Fax +86 2365463270, Email jiantenggu@hotmail.com Daqing Ma, Division of Anaesthetics, Pain Medicine and Intensive Care, Department of Surgery and Cancer, Faculty of Medicine, Imperial College London, Chelsea and Westminster Hospital, London, UK, Tel +44 020 3315 8495, Fax +44 020 3315 5109, Email d.ma@imperial.ac.ukPurpose: This study aims to investigate the cytoprotective and anti-inflammatory effects of an α2-adrenoreceptor (α2-AR) agonist, dexmedetomidine (Dex), on lipopolysaccharides (LPS)-induced acute lung injury and underlying mechanisms with focus on alveolar macrophage polarization modulation.Methods: C57BL/6 mice were intraperitoneally injected LPS (10 mg/kg) with or without Dex (25 μg/kg) and/or α2-AR antagonist atipamezole (Atip, 500 μg/kg). Lung tissues were then analysed to determine injuries. In vitro, human pulmonary epithelial cells (A549) and mice alveolar macrophages (MH-S) were exposed to LPS (10 ng/mL) with or without different concentrations of Dex (0.1- 100 nM). Alveolar macrophage polarization, NLRP3 inflammasome activation and inflammatory responses were determined. PTEN/Akt signaling and its downstream transcriptional factors as targets for macrophage polarization were assessed.Results: Dex treatment significantly reduced pro-inflammatory M1 macrophage polarization and NLRP3 inflammasome activation in the lungs relative to the mice treated with LPS. The similar pattern reduction of NLRP3 inflammasome activation by Dex was also found in A549 cells. Atip partly reversed the anti-inflammatory effects of Dex. In cultured alveolar macrophages, Dex reduced LPS-mediated expression of IL-1, − 6 and TNF-α receptors while promoting alveolar macrophages differentiation towards a M2 anti-inflammatory phenotype. Additionally, LPS increased Akt signaling activation in a time-dependent manner, which was further activated by Dex via inhibiting phosphatase and tensin homolog (PTEN). The action of Dex on Akt signaling shifted alveolar macrophages from M1 to M2 phenotype through increasing STAT6 and IRF4 transcriptional factors.Conclusion: Dex protected against LPS-induced lung injury and suppressed LPS-induced pulmonary inflammatory responses by attenuating the NLRP3 inflammasome activation and promoting anti-inflammatory M2 macrophage polarization.Keywords: sepsis, acute lung injury, macrophage polarization, dexmedetomidine, Akt signaling